Assessment of Survival of Keystone Perforator Flap - Masood Butt, Ahsan; Rao Saood Ahmad; Gazanfar Ali; Javaria Ahsan; Razia Bibi; Sohail Ilyas (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the single most important factor affecting the survival of keystone perforator flap. Study Design: Case series. Place and Duration of Study: Combined Military Hospital, Quetta Pakistan, from Mar 2021 to Sep 2022. Methodology: Patients presenting at Plastic Surgery OPD, where resultant wound defects were covered by a keystone perforator flap for wound coverage, above ten years of age were included in the study. They also included proximal forearm self-harm patients. Operated patients were followed up post-operatively for three weeks, and success and complications were noted. The single most important factor for flap complication was noted. Results: Eleven patients were studied that fulfilled the inclusion criteria. The age range was 11-59 years. Two were cases of pilonidal sinus, 1 was squamous cell carcinoma (SCC) forearm, and 1 was carbuncle back. All the remaining 7 were of selfharm scars/ wounds of the proximal forearm. Two patients developed partial peripheral flap necrosis that later healed with granulation tissue. The reason for partial flap necrosis was recognized to be shearing forces due to early/excessive post-op mobilization. Conclusion: The keystone perforator flap transposes pliable adjacent tissue, giving the patient the same look and skin texture as the original tissue. The most important factor affecting flap survival in this small case series was shearing forces, and measures to immobilize the operation site could improve results.